Quantum SWAP gate realized with CZ and iSWAP gates in a superconducting architecture - Christian Križan; Janka Biznárová; Liangyu Chen; Emil Hogedal; Amr Osman; Christopher W Warren; Sandoko Kosen; Hang-Xi Li; Tahereh Abad; Anuj Aggarwal; Marco Caputo; Jorge Fernández-Pendás; et al. (New Journal of Physics)
It is advantageous for any quantum processor to support different classes of two-qubit quantum logic gates when compiling quantum circuits, a property that is typically not present in existing platforms. In particular, access to a gate set that includes support for the CZ-, iSWAP-, and SWAP-type families of gates renders conversions between these gate families unnecessary during compilation, as any two-qubit Clifford gate can be executed using at most one two-qubit gate from this set, plus additional single-qubit gates. We experimentally demonstrate that a SWAP gate can be decomposed into one iSWAP gate followed by one CZ gate, affirming a more efficient compilation strategy over the conventional approach that relies on three iSWAP or three CZ gates to replace a SWAP gate. Our implementation makes use of a superconducting quantum processor design based on fixed-frequency transmon qubits coupled together by a parametrically modulated tunable transmon coupler, extending this platform’s native gate set so that any two-qubit Clifford unitary matrix can be realized using no more than two two-qubit gates and single-qubit gates.